Sixth NACW - Brown (iss. eds.), Kent (Rangifer, 1996)
The Sixth North American Caribou workshop was attended by over 200 people from across North America, as well as four special guests from Russia. Participants were very surprised to see and hear about caribou living in large cedar forests and on mountain-tops where snow depths exceeded several meters, and the only available forage was the lichens growing on trees. We believe that the workshop was a major success with many excellent presentations and posters, as well as opportunities for the participants to meet and discuss caribou research, ecology, and management with their counterparts from across North America. These proceedings include a wide range of excellent papers that provide a permanent record of the workshop. The editors thank the authors and reviewers for their efforts to produce and review these papers.